Literasi Keuangan Non Tunai bagi Santri Pondok Pesantren Al Falah Puteri Banjarbaru - Anwar, Mukhlis Kaspul; Malihah, Lola; Rahman, Muhammad; Rahmah, Nita (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service project aims to enhance non-cash financial literacy among female students (santriwati) at Al Falah Islamic Boarding School Puteri Banjarbaru through education on e-wallet usage. The program employed the Asset-Based Community Development (ABCD) approach, which focuses on empowering existing community assets. Activities were carried out through discovery, dream, design, delivery, and evaluation stages. The results showed improved understanding of non-cash transactions, readiness of the pesantren cooperative to manage top-up systems, and strong enthusiasm from the community for implementation. This project confirms the effectiveness of the ABCD approach in building an inclusive financial system within the pesantren environment.